Unlocking investment opportunities through grassland restoration in Colombia - Valencia Salavar, Sara (International Livestock Research Institute, 2025)
This policy brief highlights the challenges and opportunities for grassland restoration in Colombia. It emphasizes the need for coordinated action among public and private stakeholders to align environmental conservation goals with economic and social priorities. By addressing the barriers to sustainable management and promoting innovative practices, Colombia can secure the future of its grasslands while enhancing productivity and environmental sustainability.